Malaria profile and socioeconomic predictors among under-five children: an analysis of 11 sub-Saharan African countries - Anjorin, Seun; Okolie, Elvis; Yaya, Sanni (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background African region accounts for 95% of all malaria cases and 96% of malaria deaths with under-five children accounting for 80% of all deaths in the region. This study assessed the socioeconomic determinants of malaria prevalence and provide evidence on the socioeconomic profile of malaria infection among under-five children in 11 SSA countries. Methods This study used data from the 2010 to 2020 Demographic and Health Survey (DHS). The survey used a two-stage stratified-cluster sampling design based on the sampling frame of the population and housing census of countries included. Statistical analyses relied on Pearson’s χ2, using the CHAID decision-tree algorithm and logistic regression implemented in R V.4.6. Results Of 8547 children considered, 24.2% (95% confidence interval CI 23.4–25.05%) had malaria infection. Also, the prevalence of malaria infection seems to increase with age. The following variables are statistically associated with the prevalence of malaria infection among under-five children: under-five child’s age, maternal education, sex of household head, household wealth index, place of residence, and African region where mother–child pair lives. Children whose mothers have secondary education have about 56% lower risk (odds ratio = 0.44; 95% CI 0.40–0.48) of malaria infection and 73% lower (odds ratio = 0.37; 95% CI 0.32–0.43) among children living in the richest households, compared to children living in the poorest households. Conclusions The findings of this study provide unique insights on how socioeconomic and demographic variables, especially maternal education level significantly predicts under-five malaria prevalence across the SSA region. Therefore, ensuring that malaria interventions are underpinned by a multisectoral approach that comprehensively tackles the interplay of maternal education and other socioeconomic variables will be critical in attaining malaria prevention and control targets in SSA.